LMC60, a material containing low-molecular-weight chitin: degradation and effects on soil microorganisms in incubated upland soil. Issue 4 (4th July 2021) - Ootsuka, Emi; Iwasaki, Yukari; Takagi, Kenji; Saito, Akihiro
ABSTRACT: The chitin-hydrolyzed product LMC60 contains low-molecular-weight chitin (LMwC) with an average molecular weight of approximately 3, 000 and sodium chloride formed by neutralization process. LMwC and a soil amendment with LMC60 (SLMC60) showed suppressive effects on plant diseases caused by pathogenic microbes. The spectrum of plant diseases against which SLMC60 was effective is however distinct from that of chitin, implying the unique effects of SLMC60 on plants and soil microorganisms. As a part of the study to elucidate the cause of the spectrum difference between chitin and SLMC60, we report here not only the degradation profile but also the antifungal property and microbial community structure in LMC60-added soil, in comparison with those in chitin-added soil and soil without supplement. Both LMC60-added and chitin-added soils inhibited the growth of a pathogenic Fusarium oxysporum strain, compared with the soil without supplement. The declining trend in the amount of LMC60 and chitin, and the patterns of ammonium accumulation, indicated equivalent degradation profiles of LMC60 and chitin at 25°C. The number of culturable bacteria increased in soil with LMC60 and chitin, but the number of culturable fungi and content of ergosterol, which is specific to fungal cells, increased only in the soil with LMC60. The effects of LMC60 and chitin on bacterial and fungal community structures were clearly distinguishable, as follows: The relative abundance of three bacterial families (Bacillaceae, Paenibacillaceae, and Alcaligenaceae) increased significantly only with LMC60. LMC60 increased the relative abundance of the family Promicrosporaceae earlier than chitin. In terms of fungi, Fusarium increased in the presence of LMC60 and chitin, the Mortierella population expanded considerably only with chitin, and Colletotrichum and Malbranchea increased only with LMC60. These effects of LMC60 on soil microorganisms which are distinct from those of chitin might suggest its spectrum of plant disease suppression.